Increasing Pig Farming Efficiency through Feed Fermentation in the Bangun Sari Pig Farming Group, Pancasari Village - I Gusti Agus Maha Putra Sanjaya; Luh Suariani; Yan Tonga; I Gede Sutapa; Ni Ketut Mardewi; Nyoman Kaca; Ni Made Yudiastari; Ni Ketut Sri Rukmini; Gusti Ayu Dewi Seri Rejeki; Dewa Nyoman Sudita; Ni Ketut Etty Suwitari; Hanilyn A. Hidalgo; Amee Nicolas; Mia Fresindo (Asian Journal of Community Services, 2023)
Pigs are one of the livestock that have an important role in the lives of people in Bali, both as meat producers and also for traditional and religious ceremonies. The community service carried out at the Bangun Sari Pig Farm Group has contributed in the form of increasing partner knowledge about pig health management and cage sanitation as well as fermented feed production by utilizing plantation (vegetable) waste which is widely available in the surrounding environment. This activity was carried out on June 26, 2023 using the active participation method. The results of this service activity are that partners understand and are able to carry out animal health management and cage sanitation properly. In addition, farmers are also able to ferment plantation waste (vegetables) into quality pig feed so as to reduce commercial feed costs and increase the partner income.